Professor surdo : negociações de identidade no ensino superior - Oliveira, Reany de (2018)
Deaf Professor's presence in higher education causes a series of negotiations on their identity and cultural differences. These professors feel active in these negotiations. The difference of identity challenges the established negotiation relations, so arise, from the negotiations with their constant struggles, problems that affect the participation of the Deaf professor in the Institution's dynamics. This research was developed with the purpose of building possibilities to make visible and understanding the negotiations, of Deaf professor's perspective, in the face of the difficulties experienced in the encounter between the deaf and the hearing culture, in the conflicts of difference. In theoretical terms, this research will be guided by the notions of Identity with Stuart Hall (2014), Deaf Identity with Perlin (2013), Deaf Culture systematized by Strobel (2016), Differentiation with Skliar (2013), explanations of Reis (2015) on the negotiation of Deaf Professor in Higher Education, the analyzes of Castro (2017) and his research on the Deaf Professor’s performance. The research started with the question: What identity negotiation strategies Deaf professors present in higher education? The objective is identify and map the narratives of deaf teachers in higher education. Starting from the research qualitative approach, we chose to collect data through interview-narrative and constituted the analysis with the collected narratives. These narratives have been identified in order to achieve a theoretical mapping expressed in the last chapter, where the constant facts of the struggles in the negotiation of identity unfold. The results point a multitude of debates, negotiations, production of difference and their meanings.